Nursing care in the prevention and treatment of cervical cancer: an integrative review (Research, Society and Development, 2022)
Objective: to describe nursing care in the prevention and treatment of cervical cancer. Methodology: this is an integrative literature review, carried out in May 2021, according to the following research question: "what nursing care has been used in the prevention and care of women with cervical cancer?". The following descriptors were used: Cervical Neoplasms, Cervical Cancer, Nursing Care and Health Care, in the MEDLINE, BDENF and LILACS databases. 10 articles were selected. Results: the selected articles point to the nursing consultation as an important tool to carry out health education aimed at prevention, with a focus on active search and encouragement for the Pap smear test, in addition to biopsychosocial-spiritual support, request and evaluation of tests, support for client and family during diagnosis, treatments and prognosis as the main interventions to be performed by nursing. Conclusion: the nurse is an important agent active in the prevention and detection of various types of diseases and conditions in the population. In care directed to women with cervical cancer, nurses play an important role in tracking, detecting, guiding, implementing care. It is hoped that the results of this study will help nursing professionals to critically reflect on their own care practice.